Persentase dan Kualitas Karkas Itik Cihateup-Alabio (CA) pada Umur Pemotongan yang Berbeda - Putra, A.; Rukmiasih, Rukmiasih; Afnan, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
Low demand of duck meat is influenced by its quality. Generally, ducks slaughtered at 8 weeks have low carcass quality. Slaughter age is expected to influence carcass quality. Therefore, the study of carcass quality in different slaughter ages (8, 10, and 12 weeks) is needed. This research used 32 males and 18 females cihateup-alabio (CA) ducks. Ducks were grouped by hatching period. The experiment design was randomized block factorial (3x2). Treatments were slaughter age and sex. Traits measured were slaughter weight, percentage of carcass and its parts, physical and sensory quality of duck carcass. The result showed that interaction of slaughter age and sex affect slaughter weight. The higher slaughter age resulted higher breast and abdominal fat percentage, but had smaller thigh percentage. Sex had no effect on carcass percentage and its parts. Higher slaughter age and male sex showed better phisycal carcass quality. Differences in slaughter age and sex had no effect on panelist preference. This research concluded that higher slaughter age produces better carcass percentage and quality.